Pengembangan Pemberdayaan Wanita Nelayan Muncar Banyuwangi Melalui Pengembangan Model Eko-Koefisiensi - Nadya Adharani; Sulistiono Sulistiono; Feby Indriana Yusuf (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
Muncar subdistrict is an area famous for the potential of fisheries in Banyuwangi Regency. There are 11 villages in Muncar sub-district with the average livelihood of the community is as a fisherman. One of the factors of coastal areas is women, coastal women play an important role in households that rely on marine resources. In domestic economic activity, coastal women contribute and even dominate. Over time from year to year, there is a continuous exploitation of fish or marine resources in Muncar that causes difficulty in obtaining fish. Moreover, the conditions of extreme season change (catching and paceklik) make the acquisition of fishing businesses and household income of traditional fishermen decrease so that it requires income outside the capture business. It becomes the basis that the existence of women or fishermen's wives as a support for household income income is needed, but to support the potential of fishermen women in economic improvement, it is necessary to formulate a strategy of empowering women through the concept of eco-coefficient. The principle of coefficient is the production of precisely or efficiently so that it is economically and environmentally beneficial.